Vertigo and dizziness due to vertebrobasilar TIA: a prospective study - Arlindo C. Lima Neto; Ji-Soo Kim; Wanderley Marques Bernardo; Roseli Saraiva Moreira Bittar (Frontiers in Stroke, 2024)
PurposeProspective studies on vascular vertigo and dizziness (VVD) due to vertebrobasilar transient ischemic attack (VBTIA) have been sparse. This study aimed to characterize clinical features, response to treatments, and prognostic factors of VVD due to VBTIA using a cohort established in 2021.MethodsWe recruited 103 patients (58 female individuals, 56.3%), with a mean age of 70.9 ± 9.3 years (range = 37–85), between January 2021 and January 2024. All patients met the diagnostic criteria of “Probable transient VVD” published by the Bárány Society. The mean interval from symptom onset to recruitment was 11.8 months (range = 0.5–72). Treatments followed the current American Heart Association–American Stroke Association's Guidelines for Prevention of Stroke in Patients with Stroke and Transient Ischemic Attack. Patients with recurrent strokes among TIAs, and patients who were already taking an antithrombotic agent and should maintain the same regimen were excluded.ResultsImbalance (46.7%) and vertigo (39.8%) were the most frequent symptoms. The duration of attacks was <1 min in 35 patients (33.9%), 1–10 min in 34 patients (33.0%), 10–60 min in 15 patients (14.6%), and >60 min in 19 patients (18.5%). Trigger factors were reported in 20 patients (19.4%), which included eccentric neck position in 12 patients (11.7%), physical exercise in four patients (3.9%), positional changes in three patients (2.9%), and eccentric neck position and physical exercise in the remaining patient (0.9%). The frequency of attacks before the medication was 1 or <1/month in 32 (31.0%) patients, 1–4/month in 44 (42.7%) patients, 4–8/month in 21 patients (20.4%), and daily in six patients (5.9%). The treatment regimens were aspirin in 57 patients (55.3%), clopidogrel in 19 patients (18.5%), aspirin plus clopidogrel in 25 patients (24.3%), and rivaroxaban in two patients (1.9%). The attacks were reduced by 93.2% [IC 95% (88.34, 98.06), number needed to treat: 1] during the median follow-up of 12 months (range = 2–36 months). Only seven (6.8%) patients experienced a new attack with the medication. No prognostic factors could be identified for the recurrences.ConclusionVVD due to VBTIA has a broad clinical spectrum. Secondary stroke prevention is effective in VVD due to VBTIA even though no prognostic factors could be identified for symptom recurrence.